Alteration in Phospholipidome Profile of Myoblast H9c2 Cell Line in a Model of Myocardium Starvation and Ischemia. Issue 10 (16th March 2016) - Sousa, Bebiana; Melo, Tânia; Campos, Ana; Moreira, Ana S.P.; Maciel, Elisabete; Domingues, Pedro; Carvalho, Rita Pereira; Rodrigues, Teresa Ribeiro; Girão, Henrique; Domingues, Maria Rosario M.
Abstract : Myocardium infarction is one of the most deathly cardiovascular diseases. It is characterized by myocardium ischemia as a result of nutrients depletion and hypoxia. The cell can respond to this injury by autophagy or apoptosis, which determines the evolution and possible recovery of the myocardium infarction. Lipids play an important role in cardiovascular disease. However reports stating lipidome variations in cardiovascular disease are scarce and the role that lipids play in this pathological condition is not completely understood. The aim of this work was to identify changes in lipid profile of a myoblast H9c2 cell line under starvation and ischemia, to better understand and recognize new biomarkers for myocardial infarction. Lipidomic profile was evaluated by HILIC‐LC‐MS and GC‐MS. Cardiac cells showed alterations in phosphatidylcholines PC (34:1) and PC (36:2), lysophosphatidylcholines lyso PC(16:0), lysoPC(18:1) and lysoPC(18:0), phosphatidylethanolamine PE (34:1), phosphatidylserine PS (36:1), phosphatidylinositol PI (36:2), PI (38:3) and PI (38:5), sphingomyelin SM (34:1) and cardiolipins CL(68:4), CL(72:5) and CL(74:7) in ischemia and/or starvation, in comparison with control. Specific differences observed only in starvation were decrease of SM (34:1) and FA (20:4), and increase of PS (36:1). Differences observed only in ischemia were decrease of PC (36:2), lyso PC (16:0) and FA (18:1) and simultaneous increase of FA (16:0), and FA (18:0). Interestingly, PC (34:1) increased in ischemia and decreased in starvation. In conclusion, our work suggests that lipids are potential markers for evaluation of cell fate, either cell death or recovery, which will be useful to improve diagnosis and prognostic of cardiovascular diseases. J. Cell. Physiol. 231: 2266–2274, 2016. © 2016 Wiley Periodicals, Inc. Abstract : This work identified changes in lipid profile of a myoblast H9c2 cell line under starvation and ischemia by HILIC‐LC‐MS and by GC‐MS. Specific differences of starvation were observed in SM, FA e PS, while in isquemia diferences were observed in PC and LysoPC and FA. Lipids are potential markers for evaluating cell's either cell death or recovery, which will be useful to improve diagnosis and prognostic of cardiovascular diseases.